Japan's Slow Response to Improve Access to Inpatient Care for COVID-19 Patients - Nakahara, Shinji; Inada, Haruhiko; Ichikawa, Masao; Tomio, Jun (Frontiers in Public Health, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has exposed various weaknesses in national healthcare systems across the globe. In Japan, this includes the inability to promptly mobilize the resources needed to provide inpatient care in response to the rapidly increasing number of patients. Combined with unclear entry points to healthcare, particularly in emergency cases, this has led to a situation in which access to healthcare is rapidly deteriorating. This study examined problems in Japan's healthcare delivery system. While Japan's healthcare resources (e.g., hospital beds and medical personnel) are comparable to those found in other high-income countries, progress has been slow in securing beds for COVID-19 patients. In addition, the number of beds has only recently reached the levels seen in Western countries. Factors related to slow resource allocation include dispersed existing medical resources (mainly in the private sector), the lack of collaboration mechanisms among private-dominant healthcare providers and public health agencies, an inadequate legal framework for resource mobilization, the insufficient quantification of existing resources, and undesignated entry points to healthcare systems. To better prepare for future disasters, including the next wave of COVID-19, Japan urgently needs to restructure its legal framework to promptly mobilize resources, accurately quantify existing resources, introduce coordination mechanisms with functional differentiations among all community stakeholders, and clearly designate entry points to healthcare.